Awesome Families - Jenkins, Kathleen (Rutgers University Press, 2021)
In Awesome Families, Kathleen Jenkins draws on four years of ethnographic research to explain how and why so many individuals-primarily from middle- to upper-middle-class backgrounds-were attracted to this religious group that was founded on principles of enforced community, explicit authoritative relationships, and therapeutic ideals. Weaving classical and contemporary social theory, she argues that members were commonly attracted to the structure and practice of family relationships advocated by the church, especially in the context of contemporary society where gender roles and family responsibilities are often ambiguous.